Testowanie hipotezy o słabej efektywności dla rynku walutowego w Polsce - Kucharski, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Fama's efficiency theory concerns capital markets, especially stock markets. We have decided to apply his idea of the weak efficiency hypothesis to currency market in Poland. There have been chosen three most popular currencies: US dollar, euro and Swiss frank as objects of research. Obtained results have been compared with that ones for WIG20 - one of Warsaw stock indices. We have verified if quotations of USD, EUR and CHFR could have been called random, using statistical tests. Those tests have been made for two kinds of data distinguished by their frequency (daily and monthly). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 222-231